2015
DOI: 10.1080/15476286.2015.1096488
|View full text |Cite
|
Sign up to set email alerts
|

Identification of linc-NeD125, a novel long non coding RNA that hosts miR-125b-1 and negatively controls proliferation of human neuroblastoma cells

Abstract: (2015) Identification of linc-NeD125, a novel long non coding RNA that hosts miR-125b-1 and negatively controls proliferation of human neuroblastoma cells, RNA Biology, 12:12, 1323-1337

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 68 publications
(62 reference statements)
0
36
0
Order By: Relevance
“…Neuroblastoma is considered to be a common and aggressive malignancy in children. Recently, it has been increasingly recognized that dysregulation of lncRNAs is involved in the progression of neuroblastoma [23,26]. Radiotherapy has become an effective strategy for neuroblastoma treatment, however, the influence of lncRNAs on radiosensitivity of neuroblastoma cells is not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma is considered to be a common and aggressive malignancy in children. Recently, it has been increasingly recognized that dysregulation of lncRNAs is involved in the progression of neuroblastoma [23,26]. Radiotherapy has become an effective strategy for neuroblastoma treatment, however, the influence of lncRNAs on radiosensitivity of neuroblastoma cells is not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…NB is a common and aggressive malignancy in children. Recently, it has been increasingly recognized that dysregulation of lncRNAs is involved in the progression of NB [31]. Radiotherapy has become an effective strategy for treatment of NB; however, the in uence of lncRNAs on radiosensitivity of NB cells is not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, biomarkers have been identified that indicate a poor prognosis and a high-risk disease group. A cell proliferation regulator Mir-100-Let-7a-2 cluster host gene (MIR100HG) promotes neuroblastoma cell proliferation [43]. lncRNA metastasis associated lung adenocarcinoma transcript 1 (MALAT1) regulates the genes which are responsible for neuronal differentiation, angiogenesis, and migration in neuroblastoma [44][45][46].…”
Section: Epigenetic Pattern In Neuroblastomamentioning
confidence: 99%